2022
DOI: 10.1101/2022.08.26.505453
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oligomeric polymorphism of HIV-1 Vpu protein in lipid environment and in solution

Abstract: The HIV-1 encoded protein Vpu forms an oligomeric ion channel/pore in membranes and interacts with multiple host proteins to support virus lifecycle. However, Vpu molecular mechanisms are currently not well understood. The structures of full-length Vpu in its monomeric and oligomeric forms are unknown, although both the monomer and oligomer are deemed important. Here, we report on the diversity of Vpu oligomeric structures and how the environment affects the Vpu oligomer formation. We produced a uniquely desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Within the literature on Vpu, there is still ongoing debate on its oligomeric state. , There is currently no structural information on the full length Vpu forming an oligomer, but there has been one structure solved of full-length Vpu in its monomeric form. ,, Some previous studies have suggested that Vpu assembles into fixed pentameric complexes, whereas other studies found that Vpu assembles into a broader range of oligomers. , Interestingly, some previous studies suggested that higher solution ionic strengths drive Vpu to assemble into large oligomeric complexes …”
Section: Resultsmentioning
confidence: 99%
“…Within the literature on Vpu, there is still ongoing debate on its oligomeric state. , There is currently no structural information on the full length Vpu forming an oligomer, but there has been one structure solved of full-length Vpu in its monomeric form. ,, Some previous studies have suggested that Vpu assembles into fixed pentameric complexes, whereas other studies found that Vpu assembles into a broader range of oligomers. , Interestingly, some previous studies suggested that higher solution ionic strengths drive Vpu to assemble into large oligomeric complexes …”
Section: Resultsmentioning
confidence: 99%
“…37,53,54 Some previous studies have suggested that Vpu assembles into fixed pentameric complexes, 55 whereas other studies found that Vpu assembles into a broader range of oligomers. 32,[56][57][58] Interestingly, some previous studies suggested that higher solution ionic strengths drive Vpu to assemble into large oligomeric complexes. 56 Additionally, the electrophysiology assays performed revealed that single channels of Vpu had different magnitudes of ion current across the bilayer (Figure S-7).…”
Section: Hiv-vpumentioning
confidence: 99%